Total synthesis of (+/-)-allocolchicine and its analogues using Co-catalyzed alkyne [2 - Paymode, Dinesh J.; Ramana, Chepuri V. (ACS Omega, 2017)
The total synthesis of (+/-)-allocolchicine has been completed by employing cobalt-catalyzed alkyne [2 + 2 + 2]-cyclotrimerization as the key reaction. The essential diyne has been synthesized from easily available 3,4,5-trimethoxybenzaldehyde following simple chemical transformations. In general, the cycloaddition gave a mixture of C(9) and C(10) isomers thus allowing the synthesis of both allocolchicine and its C(10)-carboxylate. Because this cycloaddition was employed at the penultimate stage, it allowed the synthesis of various analogues having the diverse functionality at C(9) and/or C(10) of ring C.